Human Capital as Engine of Growth the Role of Knowledge Transfers in Promoting Balanced Growth within and across Countries - Isaac Ehrlich; Yun Pei (Institute of Labor Economics (IZA), 2020)
Unlike physical capital, human capital has both embodied and disembodied dimensions. It can be perceived of as skill and acquired knowledge, but also as knowledge spillover effects between overlapping generations and across different skill groups within and across countries. We illustrate the roles these characteristics play in the process of economic development; the relation between income growth and income and fertility distributions; and the relevance of human capital in determining the skill distribution of immigrants in a balanced-growth global equilibrium setting. In all three illustrations, knowledge spillover effects play a key role. The analysis offers new insights for understanding the decline in fertility below population replacement rate in many developed countries; the evolution of income and fertility distributions across developing and developed countries; and the often asymmetric effects that endogenous immigration flows and their skill composition exert on the long-term net benefits from immigration to natives in source and destination countries.
Keywords: F22; F43; J11; J24; O15; 330; human capital; economic growth; demographic change; endogenous immigration; income distribution